Preclinical Evaluation of a Single Intravenous Infusion of hUC-MSC (BX-U001) in Rheumatoid Arthritis. (13th October 2020) - Liu, Linan; Farhoodi, Henry P.; Han, Menglu; Liu, Guangyang; Yu, Jingxia; Nguyen, Lily; Nguyen, Brenda; Nguyen, Agnes; Liao, Wenbin; Zhao, Weian
Rheumatoid arthritis (RA) is an inflammatory disease of the joints, which causes severe pain and excessive systemic circulation of harmful inflammatory cytokines. Current treatments are limited, with some patients not responding well, and some experiencing severe and detrimental side effects. Mesenchymal stem cells (MSC) are cell-based therapeutics being evaluated as potent immunomodulators in RA and may provide relief to patients not responding well to drug-based treatments. We evaluated the safety and efficacy of BX-U001 human umbilical cord tissue–derived mesenchymal stem cells (hUC-MSC) to treat RA, in support of a successful investigational new drug application. A collagen-induced arthritis (CIA) mouse model of RA was established in DBA/1 J mice. Mice from the treatment assessment group were given a tail vein infusion of hUC-MSC 24 days after primary RA induction, while control assessment (CA) group mice were given cell-free carrier solution. All animals were evaluated daily for RA symptoms via clinical scoring, blood was taken periodically for cytokine analysis, and mice were dissected at end point for histological analysis. A linear mixed model was used to compare the rate of change among groups. The clinical scores of TA group were significantly reduced compared with CA group ( P < 0.01), indicating therapeutic effects. The histological scores of the joints in TA group were significantly lower than those in the CA group ( P < 0.05), but had no significant difference compared with Healthy groups ( P > 0.05). The concentration of (interleukin) IL-6 in TA group was significantly reduced by 80.0% ( P < 0.0001) 2 days after treatment and by 93.4% at the experimental endpoint compared with levels prior to hUC-MSC injection. A single intravenous infusion of hUC-MSC (2 × 10 6 cells/mouse), to CIA-induced DBA/1 J mice, resulted in significant alleviation of RA symptoms and may provide significant therapeutic benefits in humans.